Crustal and upper-mantle structure beneath ice-covered regions in Antarctica from S-wave receiver functions and implications for heat flow. Issue 3 (28th January 2016) - Ramirez, C.; Nyblade, A.; Hansen, S.E.; Wiens, D.A.; Anandakrishnan, S.; Aster, R.C.; Huerta, A.D.; Shore, P.; Wilson, T.
Abstract: S -wave receiver functions (SRFs) are used to investigate crustal and upper-mantle structure beneath several ice-covered areas of Antarctica. Moho S-to-P (Sp) arrivals are observed at ∼6–8 s in SRF stacks for stations in the Gamburtsev Mountains (GAM) and Vostok Highlands (VHIG), ∼5–6 s for stations in the Transantarctic Mountains (TAM) and the Wilkes Basin (WILK), and ∼3–4 s for stations in the West Antarctic Rift System (WARS) and the Marie Byrd Land Dome (MBLD). A grid search is used to model the Moho Sp conversion time with Rayleigh wave phase velocities from 18 to 30 s period to estimate crustal thickness and mean crustal shear wave velocity. The Moho depths obtained are between 43 and 58 km for GAM, 36 and 47 km for VHIG, 39 and 46 km for WILK, 39 and 45 km for TAM, 19 and 29 km for WARS and 20 and 35 km for MBLD. SRF stacks for GAM, VHIG, WILK and TAM show little evidence of Sp arrivals coming from upper-mantle depths. SRF stacks for WARS and MBLD show Sp energy arriving from upper-mantle depths but arrival amplitudes do not rise above bootstrapped uncertainty bounds. The age and thickness of the crust is used as a heat flow proxy through comparison with other similar terrains where heat flow has been measured. Crustal structure in GAM, VHIG and WILK is similar to Precambrian terrains in other continents where heat flow ranges from ∼41 to 58 mW m −2, suggesting that heat flow across those areas of East Antarctica is not elevated. For the WARS, we use the Cretaceous Newfoundland–Iberia rifted margins and the Mesozoic-Tertiary North Sea rift as tectonic analogues. The low-to-moderate heat flow reported for the Newfoundland–Iberia margins (40–65 mW m −2 ) and North Sea rift (60–85 mW m −2 ) suggest that heat flow across the WARS also may not be elevated. However, the possibility of high heat flow associated with localized Cenozoic extension or Cenozoic-recent magmatic activity in some parts of the WARS cannot be ruled out.